Sistem Pendeteksian Lahan Parkir Kosong pada Static Image dengan Image Processing - Albert Liem; Iwan Njoto Sandjaja; Rudy Adipranata (Jurnal Infra, 2017)
In this paper we will explain about vacant parking space detection system through image processing. This program was made with Visual Studio using C++ programming language and OpenCV library. Image processing itself has a vast research area and some of its methods will be used to create a parking space detection system. In this program, the input consists of the video feed of the parking lot, the said video is processed and analyzed with thresholding classification and SVM classification, resulting in an indicator to show if certain parking slot is vacant or not.